DIREITO À EDUCAÇÃO INFANTIL EM MUNICÍPIOS PARANAENSES: RELAÇÕES ENTRE SISTEMAS DE ENSINO E PLANOS MUNICIPAIS DE EDUCAÇÃO - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2017)
This study aims to study the Municipal Plans of Education of the State of Paraná. The objective of the research is to analyze how these SMEs are placed the right to Infant Education and the indicatives for its effectiveness. The problem that led to the analysis was thus defined: How are the Municipal Plans foreseen the legal challenges to be faced to guarantee the right of children from zero to five years to Early Childhood Education? And, what are the specific actions that determine the guarantee of the effectiveness of these rights? It is a bibliographical and documentary research, having as centrality the Municipal Plans of Education of the municipalities of Paraná that have already instituted their own Teaching Systems. The method used to analyze the context of the research was the historical and dialectical materialism, through the contribution to understand the social, political and economic dynamics of the present society, through the contradictions evidenced by it. The analyzes used were: UNICEF Reports (2006, 2009, 2012, 2016) that explore the issue of the situation of children and the child. In the aspects of the historicity of the infantile education the contributions of: Kuhlmann (1998; 2001; 2011), Kramer (2006), Nunes; Corsino; Didonet (2011), among others. For the understanding of Early Childhood Education and its condition in capitalist society, we endorse Marx (1996, 1997, 1999, 2004, 2008, 2013), Gramsci (2001), Mészaros (2008). The legal framework is also used from the Federal Constitution (1988), ECA (1990), LDBEN (9394/1996) and PNE (2014). For the analysis of the Education Plans we use the works of Saviani (1999, 2007, 2014), Cury (1998, 2000), Dourado (2010, 2014, 2016), among others. Based on the limits and possibilities evidenced in the Municipal Plans analyzed, in comparison with the theoretical reference of support and the data on the attendance of the age group, it is pointed out the contradictions with regard to the attendance to Infant Education: while the legislation indicates advances The reality of the municipalities shows the distance to make them effective in practice. Finally, based on the analysis, the research results indicate that despite the acknowledged advances that Brazilian legislation has given to children's rights, these are at risk
Keywords: Direito à Educação Infantil; Políticas Educacionais; Sistemas de Ensino; Planos Municipais de Educação; Right to early childhood education; Educational Politics; Teaching Systems; Municipal Plans of Education; CNPQ::CIENCIAS HUMANAS::EDUCACAO